A Femtocell Cluster Based Cache Handover Strategy - Jihong Zhao; Xun Wang; Zhirong Luan (Dianxin kexue)
To improve the quality of indoor wireless communication,the femtocell begins to be deployed in different indoor wireless communication scenarios.In the densely deployed femtocell network,when users handover from the macrocell to the femtocell,the multiple RSRP from different femtocell seriously affect the accuracy of the handover process.To solve above problems,the idea of femtocell cluster was proposed to improve the handover accuracy and reduce the unnecessary handover.In addition,a cache handover strategy was proposed to improve the efficiency of handover from macrocell to femtocell.Simulation results verify the proposed algorithms and strategies.